The Effectiveness Of Al-Quran Reading And Writing (Btq) In Improving Al-Quran Reading Ability For Students Of Class VII Of SMP Negeri 10 Satap Sayan - Parida; Sukino; Erwin (IJGIE (International Journal of Graduate of Islamic Education), 2023)
For a Muslim, the Qur’an is a sacred book. When there is a problem related to the way of life, thinking, or Islamic values, then the Qur’an should be the first reference to use. Therefore, it is very important for Muslims to be able to read and practice the content of the Qur’an. However, today we can see that fewer and fewer homes have the Qur’an, and many Muslims can’t read it. This is very worrisome because it can make someone more and more distant from the teaching of the Prophet. Therefore, all parties, not only religious or BTQ teachers, but also teachers from other subjects and society, should take an active part in enhancing the culture of reading the Qur’an among Muslim families. Through the reading of the Qur’an, one can gain happiness in this world and in the Hereafter. The purpose of this study is to describe the implementation of the Reading Al-Quran program in SMP.Negeri 10 Satap Sayan Dusun Nanga Sasak, Desa Pekawai, Kec. Sayan and also to evaluate the effectiveness of the program in improving the ability to read the Qur’an in the school. This research was carried out in the field (field research) and data sources obtained from SMP.Negeri 10 Satap Sayan Dusun Nanga Sasak, Desa Pekawai, Kec. Sayan, with research subjects such as the Head of School, Teacher Reading the Quran, and students. Data collection methods include interviews, observations, and documentation, and data analysis using deductive analysis methods. In this study, it was found that the activity of Reading the Qur'an in the SMP.Negeri 10 Satap Sayan, Dusun Nanga Sasak, Desa Pekawai, Kec. Sayan is done at effective hours in the morning with a duration of 1 hour lessons per week for each class. The main teaching is to read the Qur’an and to remember Chapter 30. The results of the study showed that the activity of reading the Quran was effective in improving the ability of students to read the Qur’an. Of the 51 students in classes VII C and VII D who attended the program, as many as 27 students or 52.9% showed improved ability to read the Qur’an..